Techno-economic Assessment of Thermal Co-pretreatment and Co-digestion of Food Wastes and Sewage Sludge for Heat, Power and Biochar Production. (May 2017) - Kempegowda, Rajesh S.; Skreiberg, Øyvind; Tran, Khanh-Quang; Selvam, P.V.P.
Abstract: This study deals with techno-economic assessments of three system scenarios combining various conversion technologies including co-digestion, hydro-methanation, syngas production and integration, thermodynamic and electrochemical aspects of a solid oxide fuel cell (SOFC) system, as well as solving the problem of chemical equilibrium in complex systems. Aspen Plus and SuperPro software packages are used as simulation and optimization tools. The optimized results are compared with other studies and reveals that thermal co-treatment integrated with a two-stage bio-thermal process involving anaerobic digestion and hydrogasification can produce good quality biofuels for a SOFC system. The economics of the final selected thermal co-treatment hybrid process for processing 30000 tons per annum of dry solids is feasible at an electricity selling cost of 0.3 $/kWh, providing project benefits such as an IRR of 29.7%, a benefit to cost ratio of 1.38 and a net present value of 123 million $. This innovative scheme not only reduces CO2 but also improves the economic return and reduces the waste discharge.